Textocentic approach at the lessons of Ukrainian language as a foreign language for medical students - Родчин, Зоряна (Educational Dimension, 2015)
Rodchyn Z. Ya. Textocentic approach at the lessons of Ukrainian language as a foreign language for medical students. The object of this research work is textocentic approach at the lessons of Ukrainian language as a foreign language for medical students. Out of four types of speech activities the most important attention is paid to reading. A small amount of exercises which assist to develop future doctors’ professional speech is presented in the article.